“Older people are weak”: perceptions and meanings of ageing and abuse against older people - Dias, Isabel; Fraga, Silvia (Frontiers in Sociology, 2024)
This paper addresses the broader issue of elder abuse and seeks to analyse how victims and non-victims of abuse connect and explain the perception of ageing and the phenomenon of violence against older people. A qualitative study was conducted based on evidence gathered through 45 semi-structured interviews with people aged 60 or above who are part of the Portuguese EPIPorto population cohort. The interviews were analysed using grounded theory. The results show that respondents link the ageist narratives that exist in our societies to the prevalence and naturalisation of violence against older people, that the risk of abuse increases with the weakening of family support networks, and that abuse is both a manifestation of asymmetrical power relations between victims and perpetrators and a severe violation of human rights. The findings also highlight the need to broaden the concept of violence against older people to include offences in the public sphere and not just in the context of the family and institutions.